GENDER DIFFERENCES IN ORGANIZATIONAL COMMITMENT: A CASE STUDY OF PUBLIC BANK EMPLOYEES IN THAILAND - Promsri, Chaiyaset (International Journal For Research In Business, Management And Accounting, 2020)
Organizational commitment has increasingly become one of the most interesting areas of management and organizational behaviors in the past years. Numerous studies attempted to investigate the relations between gender and organizational commitment to examine whether men and women differ in commitment. These studies reported contradictory findings in particular in a public bank in Thailand, which many studies found no significant difference between males and females in organizational commitment. Hence, the purpose of this present study is to explore the differences between male and female employees in organizational commitment. A sample of 143 employees who worked at a selected public bank headquarters was gathered data through a survey questionnaire. Results of independent samples t-test analysis indicated that there was no significant difference between male and female employees of this bank in affective commitment and normative commitment while continuance commitment was found a significant difference between males and females (t=3.133, p = .002). Male employees were reported to have a higher continuance commitment than female employees. Discussion and recommendations for future studies were also discussed.